2020
DOI: 10.1155/2020/5651780
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Human Gingival Fibroblast Response and Reduced Porphyromonas gingivalis Adhesion with Titania Nanotubes

Abstract: Successful dental implants rely on stable osseointegration and soft-tissue integration. Titania nanotubes (TNTs) with a diameter of 100 nm could increase the mesenchymal stem cell response and simultaneously decrease Staphylococcus aureus adhesion. However, the interactions between the modified surface and surrounding soft tissues are still unknown. In the present study, we fully investigated the biological behavior of human gingival fibroblasts (HGFs) and the adhesion of Porphyromonas gingivalis (P. gingivali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 44 publications
3
28
0
Order By: Relevance
“…Depending on the general shape in terms of length, width and distances between these pillars, different effects such as penetration, rupture of the membrane through stretching or buckling of the bacterial wall are discussed as the actual antibacterial effect [7]. Titania nanotubes with a diameter of 100 nm could successfully enhance gingival fibroblast proliferation and attachment while reducing the adhesion of P. gingivalis [14]. In this regard, there seem to be different targets in terms of how a nanostructure should be designed, and implants with such surfaces have not yet been introduced into the field.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the general shape in terms of length, width and distances between these pillars, different effects such as penetration, rupture of the membrane through stretching or buckling of the bacterial wall are discussed as the actual antibacterial effect [7]. Titania nanotubes with a diameter of 100 nm could successfully enhance gingival fibroblast proliferation and attachment while reducing the adhesion of P. gingivalis [14]. In this regard, there seem to be different targets in terms of how a nanostructure should be designed, and implants with such surfaces have not yet been introduced into the field.…”
Section: Introductionmentioning
confidence: 99%
“…Capelatto et al [ 19 ] verified that titanium nanotube samples presented a significant effect on the number of cells present, showing an increase of cells from day 1 to day 7. The cell proliferation assay results showed that titanium nanotubes (100 nm) could promote high cell proliferation compared with control Ti [ 29 ]. Furthermore, Ti nanotube alloys can induce cell growth and biocompatibility in stem cells after one and seven days in culture [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed cells on the nanotube titanium sheets (100 nm or 150 nm) by SEM. In addition, titanium nanotubes with a diameter of 100 nm promoted cell attachment of human gingival fibroblasts [ 29 ]. Kumeria et al [ 13 ] reported that an advanced biopolymer-coated drug-releasing titanium nanotubes implant enhanced osteoblast adhesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, no HGF adhesion was observed at 24, 72, and 150 h, suggesting that P. gingivalis had an adverse effect on HGF cell adhesion and proliferation. This adverse bacterial effect on cell adhesion has been suggested to result from alteration of the extracellular matrix and its components [33][34][35][36] . Propidium iodide signals, which represented dead bacteria, were more intense than SYTO 9 signals, which represented live bacteria in all groups (Fig.…”
Section: Discussionmentioning
confidence: 99%